MAIN TRENDS IN THE FORMATION OF RURAL SETTLEMENTS IN THE TERRITORY OF TARA (THE IRTYSH AREA) BETWEEN 1920 AND 1980 - Evgenia Valeryevna SOKOLOVA; Dmitry Viktorovich KUZNETSOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This article is concerned with studying the main trends connected with the changes of the borders of the Tara Irtysh area in the Soviet era. A wide range of sources, including some unconventional sources untypical of historical surveys (oral historical materials), was used as the basis of the research. The cumulative analysis of the above-mentioned sources enabled us to study the problem comprehensively, i.e. from the position of an inhabitant of the Irtysh area – the direct creator of history. The features of the used sources, the research object and its objective determined the basic tools that combined principles and methods generally accepted in historical science with peculiarities of new local history and rural history that were actively developing. In the course of the study, we have paid much attention to the factors determining the transformation of the rural settlement network under consideration throughout the designated period. We believe that the main factor was the state policy in the agrarian sphere. Among the reasons for the reduction in the number of villages were the policy of consolidation of the farms and the outflow of their population to cities, regional centers, and larger villages where the state planned to build central estates with a well-developed infrastructure.